Effect of Transition Metal Ions on the Oxidation of Benzaldehyde by Bromine - Dayalan, A.; MARTIN, S. (Asian Journal of Chemistry, 2010)
The kinetics of transition metal ion catalyzed oxidation of benzaldehyde by bromine in aqueous acetic acid was studied iodimetrically. The reactions were monitored at different conditions such as change in concentration of bromine, benzaldehyde, solvent composition (acetic acid-water), ionic strength and temperature. Kinetic parameters such as specific reaction rate, energy of activation, enthalpy of activation, entropy of activation and free energy of activation were evaluated. Typical values observed are: kobs = 1.16 × 10-4 s-1, ΔE# = 78.05 kJmol-1, ΔH# = 75.43 kJ mol-1, ΔS# = -71.14 J K-1 mol-1 and lnA = 21.96 for the uncatalysed reaction. Transition metal ions were found to act as mild catalyst and the catalytic activity of the ions studied was found to be in the order: Fe3+ > Co2+ > Mn2+ >Ni2+ >Zn2+.